Ecological responsibility of tourism - Beljanski Nevena (University Educons, Faculty of Sports and Tourism, Novi Sad, 2018)
Sustainable tourism aims to make tourists achieve their goals in the so-called ecodestinations, while not destroying what attracted them. Ecodestinations attract modern tourists by providing them with a sense of closeness to the environment, natural values and the local community, in accordance with the accepted concept of sustainable development. Ecotourism represents a friendly journey to environment; it emphasizes the observation and preservation of natural habitats and archeological resources, represents a means of environmental protection, ecologically responsible tourism and a way of protecting natural areas that entails economic earnings through the protection of natural resources. The basic principles of ecotourism are minimisation of the negative impacts on nature and culture that can damage the destination, education of travellers about the importance of protection, direct income from protection, as well as management of natural and protected areas. While travellers around the world are looking for travel that is full of activities in nature, cultural and recreational content, ecotourism in Serbia is quite underdeveloped. Positive aspects need to be encouraged and maximized and negative ones mitigated and neutralized in order to achieve ecologically responsible tourism.